Nutritional content in Eucalyptus benthamii mini-stump leaves - Brondani, Gilvano Ebling; Baccarin, Francisco José Benedini; Gonçalves, Antônio Natal; Almeida, Marcílio de (Acta Scientiarum. Agronomy, 2014)
The aim of this study was to evaluate the foliar nutrient content in Eucalyptus benthamii mini-stumps treated with different Zn and B concentrations during successive shoot collections. Shoots were collected from mini-stumps fertigated with nutrient solutions containing different concentrations of Zn and B (S1 – free of Zn and B; S2 – 0.5 mg L-1 Zn; S3 – 0.5 mg L-1 B; S4 – 0.5 mg L-1 Zn and B; S5 – 1.0 mg L-1 Zn and B; S6 – 2.0 mg L-1 Zn and B). Eight shoot collections from the clonal mini-garden were performed. For each shoot collection, the nutritional content of the leaf was determined (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn). The experiment was conducted using a randomized design with a split plot and included three replications. The foliar macro and micronutrient contents varied significantly in relation to the treatments, and the S5 and S6 nutritive solutions presented the best responses.